Fundamental Values at the Crossroads Between Politics, Policy, and Research - Bergan, Sjur (International Higher Education, 2025)
<h3 id="the-fundamental-values-of-higher-education-have-become-the-subject-of-political-debate-policy-measures-and-increased-academic-attention-largely-due-more-to-a-backlash-against-democracy-than-to-any-concerns-about-quality-this-article-describes-such-developments-in-europe-and-suggests-elements-that-could-be-included-in-a-strengthened-research-agenda-that-has-academic-as-well-as-political-and-policy-relevance" data-pm-slice="1 1 []">The fundamental values of higher education have become the subject of political debate, policy measures, and increased academic attention, largely due more to a backlash against democracy than to any concerns about quality. This article describes such developments in Europe and suggests elements that could be included in a strengthened research agenda that has academic, as well as political and policy relevance.